Stimulating cROSstalk between commensal bacteria and intestinal stem cells - Patel, Parthive H.; Maldera, Julieta; Edgar, Bruce (The EMBO journal, 2013)
Commensal gut bacteria benefit their host is many ways. New findings report that commensal bacteria also promote intestinal epithelial renewal in both flies and mice.
Gesehen am 20.12.2021